An update on the feeding habits of fish in the Mediterranean Sea (2002-2015) - KARACHLE, P. K.; STERGIOU, K. I. (Mediterranean Marine Science, 2017)
In this study we updated the previous compilation of the feeding habits and trophic levels (TROPHs) of Mediterranean fish. In total, 172 publications were retrieved and analysed. Collected data refer to 146 species, with a TROPH value ranging from 2.00 to 4.54. The analysis of TROPH distribution verified the previously proposed classification of species into functional trophic groups. Overall, information on diet composition exits for 203 fish species out of the >700 fishes from the Mediterranean, a fact clearly showing that feeding habits are understudied despite their importance in ecological applications and fisheries management. More than half (60.6%) of these species are classified as omnivores with preference to animal material, 36.5% are carnivores, 1.9% are omnivores with preference to plants, and two (i.e. Siganus luridus and S. rivulatus) are pure herbivores. Finally, towards the direction of filling in information gaps, recommendations for future research are given.